Ex Libris Inż. Stanisław Majewski / P. Steller. - Steller, Paweł (1895-1974) ([wydawca nieznany], 1955)
Na tle kryształów, tarcza ze skrzyżowanymi dwoma młotkami, napis u góry: Ex Libris, u dołu: Inż. Stanisław Majewski.